Uptake and continuation of HIV pre‐exposure prophylaxis among women of reproductive age in two health facilities in Kisumu County, Kenya. Issue 3 (13th March 2023) - Ogolla, Mercelline; Nyabiage, Omoto Lennah; Musingila, Paul; Gachau, Susan; Odero, Theresa M. A.; Odoyo‐June, Elijah; Ochanda, Boniface; Appolonia, Aoko; Katiku, Elizabeth; Joseph, Rachael; Ogolla, Cirrilus; Otieno, Linda; et al.
Abstract: Introduction: In 2020, Kenya had 19, 000 new HIV infections among women aged 15+ years. Studies have shown sub‐optimal oral pre‐exposure prophylaxis (PrEP) use among sub‐populations of women. We assessed the uptake and continuation of oral PrEP among women 15–49 years in two health facilities in Kisumu County, Kenya. Methods: A retrospective cohort of 262 women aged 15–49 years, initiated into oral PrEP between 12 November 2019 and 31 March 2021, was identified from two health facilities in the urban setting of Kisumu County, Kenya. Data on baseline characteristics and oral PrEP continuation at months 1, 3 and 6 were abstracted from patient records and summarized using descriptive statistics. Missing data in the predictor variables were imputed within the joint modelling multiple imputation framework. Using logistic regression, we evaluated factors associated with the discontinuation of oral PrEP at month 1. Results: Of the 66, 054 women screened, 320 (0.5%) were eligible and 262 (82%) were initiated on oral PrEP. Uptake was higher among women 25–29 years as compared to those 15–24 years (77% vs. 33%). Oral PrEP continuation declined significantly with increasing duration of follow‐up; 37% at month 1, 21% at month 3 and 12% at month 6 ( p <0.05). In the adjusted analysis, women 15–24 years had lower adjusted odds of continuing at month 1 than women ≥25 years (adjusted odds ratio [aOR]: 0.41, 95% CI: 0.21–0.82). There was no association between being sero‐discordant and continuation of oral PrEP at month 1 (aOR; 1.21, 95% CI 0.59–2.50). Women from the sub‐county hospital were more likely to continue at month 1 of follow‐up compared to women enrolled in the county referral hospital (aOR 5.11; 95% CI 2.24–11.70). Conclusions: The low eligibility for oral PrEP observed among women 15–49 years in an urban setting with high HIV prevalence calls for a review of the screening process to validate the sensitivity of the screening tool and its proper application. The low uptake and continuation among adolescent girls and young women underscores the need to identify and address specific patient‐ and facility‐level barriers affecting different sub‐populations at risk for HIV acquisition.